PILIHAN STRATEGI PEMASARAN UNTUK MENINGKATKAN DAYA SAING UMKM KOTA JAMBI - Efandri Agustian; Indah Mutiara; Adria Wuri Lastari (Asosiasi Dosen Akutansi Indonesia, KEPRI, 2022)
The development of information and technology causes fierce business competition, causing micro, small and medium enterprises (MSMEs) to be able to survive and compete for market share by implementing strategies, concepts and good management designs. Management is the key factor for success in the era of technology and information nowadays in order to create opportunities for its products. The purpose of this activity is to determine the strengths, weaknesses, opportunities and threats, to compile IFAS (Internal Factor Analysis Summer) and EFAS (External Factor Analysis Summer) and to find out a good marketing strategy after analyzing with SWOT (Strength, Weakness, Opportunity, Threat). The phenomenon that exists, MSME entrepreneurs facing fierce competition is marked by the proliferation of products from outside the region. This study uses the SWOT analysis method to identify the company's internal and external factors.